2010
DOI: 10.1007/s00330-009-1702-1
|View full text |Cite
|
Sign up to set email alerts
|

Widening of coronary sinus in CT pulmonary angiography indicates right ventricular dysfunction in patients with acute pulmonary embolism

Abstract: Width of the coronary sinus seems to be a promising parameter for identification of RVD in patients with acute PE. A prospective study should be undertaken to further assess its clinical and prognostic applicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Modern pCTA is capable of clearly illustrating intraluminal clots up to subsegmental arteries [7,8]. Besides, the method can point out indirect effects of PE to the cardiac level with changes in vessel diameters, interventricular septum deviation, and reflux of contrast medium into the venous system (VCR) [5,6,9]. The severity of PE can be evaluated with CTA by using different scoring systems that were derived from conventional angiography studies [10] and adapted to pCTA [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Modern pCTA is capable of clearly illustrating intraluminal clots up to subsegmental arteries [7,8]. Besides, the method can point out indirect effects of PE to the cardiac level with changes in vessel diameters, interventricular septum deviation, and reflux of contrast medium into the venous system (VCR) [5,6,9]. The severity of PE can be evaluated with CTA by using different scoring systems that were derived from conventional angiography studies [10] and adapted to pCTA [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…After screening by title and abstract and full‐text review, 26 studies ( n = 3508 patients) were included (Figure 1). 11–36 Study characteristics are shown in Table 1, with further details in Table S1. The mean or median age of included patients ranged from 41 to 70 years and between 20% and 64% were female.…”
Section: Resultsmentioning
confidence: 99%
“…All echocardiography in included studies was transthoracic echocardiography. The individual measures used to assess RV dysfunction on CT scan were increased RV/LV ratio with varying cutoffs (24 studies 11–22,24–28,30–36 ), pulmonary artery measurement (six studies 12,17,22,28–30 ), RV size (two studies 22,30 ), vena cava size (three studies), 22,25,30 coronary sinus size (two studies), 22,30 and aortic valve dimensions (one study 30 ). Other individual parameters included reflux of contrast into the IVC (IVC reflux, four studies) 17,21,22,28 and interventricular septal deviation (five studies 17,21,22,28,33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies these parameters were mainly analyzed: pulmonary artery/aorta ratio, right ventricular/left ventricular ratio, pulmonary obstruction index (POI), ventricular septal bowing (VSB) and venous contrast reflux (VCR) (ref. [12][13][14][15] ). In our study, we used pulmonary artery normalized diameter (nPA), PA/Ao ratio, RV CT/LV CT ratio in comparison with echocardiography parameters -normalized right ventricular diastolic diameter (nRV echo) and RV/LV diastolic diameter ratio (RVecho/LV echo).…”
Section: Introductionmentioning
confidence: 99%